COVID-19 Pandemic and its Impact on the Management of Head and Neck Cancer in the Spanish Healthcare System. - Mayo-Yáñez, Miguel; Palacios-García, José M.; Calvo-Henríquez, Christian; Ayad, Tareck; Saydy, Nadim; León, Xavier; Parente, Pablo; Chiesa-Estomba, Carlos Miguel; Lechien, Jérôme R. (International Archives of Otorhinolaryngology, 2021)
Introduction Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has represented a major challenge for healthcare systems worldwide, changing the habits of physicians. A reorganization of healthcare activity has been necessary, limiting surgical activity to essential cases (emergencies and oncology), and improving the distribution of health resources.Objective To analyze the impact of the COVID-19 pandemic on head and neck cancer surgery management in Spain.Methods A cross-sectional study, through an anonymous and voluntary online survey distributed to 76 Spanish otorhinolaryngology departments.Results A total of 44 centers completed the survey, 65.9% of which were high-volume. A total of 45.5% of them had to stop high-priority surgery and 54.5% of head and neck surgeons were relocated outside their scope of practice. Surgeons reported not feeling safe during their usual practice, with a decrease to a 25% of airway procedures. A total of 29.5% were “forced” to deviate from the “standard of care” due to the epidemiological situation.Conclusions Approximately half of the departments decreased their activity, not treating their patients on a regular basis, and surgeons were reassigned to other tasks. It seems necessary that the head and neck surgeons balance infection risk with patient care. The consequences of the reported delays and changes in daily practice should be evaluated in the future in order to understand the real impact of the pandemic on the survival of head and neck cancer patients.
Keywords: COVID-19; coronavirus; otolaryngology; aerosol generating procedures; personal protective equipment; cancer treatment; head neck surgery; mortality; morbidity